Pengembangan Produk Nutrasetika Bahan Alam di Kelompok Wanita Tani Cemara Banjarbaru - Astuti, Karunita Ika; Noviadi, Aditya; Wahyudin, Wahyudin; Hidayatullah, Muhammad (Penerbit Goodwood, 2023)
Purpose: Kelompok Wanita Tani (KWT) Cemara is a program that develops agricultural products from Landasan Ulin Tengah in the Liang Anggang District, Banjarbaru. Product feels have not been a massive number of simply processed snack products. The nutritional snack product has the potential to be developed considering that human and natural factors are very abundant but have not been empowered and organized. The introduction of nutraceutical theory and the potential from Landasan Ulin Tengah Village likely moringa leaves and swamp sepat fish. Furthermore, activities include training on the manufacture of nutraceuticals and marketing products.Research methodology: KWT Cemara as partners participated in UPT BPP Liang Anggang enthusiastically according to the schedule. The target of the activity of KWT Cemara follows very well and can be understood with the material.Results): The participants were very enthusiastic and reluctant to ask questions if they did not understand the demonstration of the materials.Limitations: Can assistance in marketing products that can be made by the public and provide education for PIRT or halal certificates for nutraceutical products.Contribution : This activity be useful for the products that can be developed by KWT Cemara